2015
DOI: 10.1016/j.ecoenv.2015.04.034
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in toxicity of wastewater from three wastewater treatment plants to alga (Scenedesmus obliquus) in northeast China

Abstract: The toxicity of municipal wastewater to the receiving water bodies is still unknown, due to the lack of regulated toxicity based index for wastewater discharge in China. Our study aims at gaining insight into the acute toxic effects of local municipal wastewater on alga, Scenedesmus obliquus. Four endpoints, i.e. cell density, chlorophyll-A concentration, superoxide dismutase (SOD) activity and cell membrane integrity, of alga were analyzed to characterize the acute toxicity effects of wastewater from municipa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 46 publications
(49 reference statements)
2
21
0
Order By: Relevance
“…In this study, poor correlations obtained between chronic toxicity using P. subcapitata and some physicochemical parameters may indicate that the growth inhibition as an endpoint is not sensitive enough to detect these relationships. These findings are confirmed in a recent study of Zhang et al [48]. In fact, the chlorophyll-A synthesis of Scenedesmus obliquus appears more sensitive than biomass and showed significant positive correlations with the concentrations of TP (r = 0.793, p = 0.004) and total organic carbon TOC (r = 0.727, p = 0.011), NH 3 -N (r = 0.555, p = 0.077) and COD (r = 0.545, p = 0.083) [48].…”
Section: Correlation Analysis Between Ecotoxicity and Physicochemicalsupporting
confidence: 88%
“…In this study, poor correlations obtained between chronic toxicity using P. subcapitata and some physicochemical parameters may indicate that the growth inhibition as an endpoint is not sensitive enough to detect these relationships. These findings are confirmed in a recent study of Zhang et al [48]. In fact, the chlorophyll-A synthesis of Scenedesmus obliquus appears more sensitive than biomass and showed significant positive correlations with the concentrations of TP (r = 0.793, p = 0.004) and total organic carbon TOC (r = 0.727, p = 0.011), NH 3 -N (r = 0.555, p = 0.077) and COD (r = 0.545, p = 0.083) [48].…”
Section: Correlation Analysis Between Ecotoxicity and Physicochemicalsupporting
confidence: 88%
“…The biological effects of wastewater on algae have been evaluated in some locations overseas, which have reported that some wastewater has had biologically harmful effects on algae, and that wastewater treatment decreased these effects [1][2][3][4]. In Japan, the Ministry of the Environment has considered the introduction of the Whole Effluent Toxicity test [5] (named J-WET in this paper) for the management of chemicals in wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…Surujlal-Naicker et al (2015) studied the toxicity of estrogenic hormones and the removal of toxicity in full-scale WWTPs using the marine bacterium, Vibrio fischeri to determine ifthere was a correlation between the hormones and the toxicity in the effluents. The results of this study revealed that the toxicity of the influent could be reduced to a certain extent in the biological treatment and that the residual estrogen contents as well as the toxicity could be reduced in certain WWTPs as well Zhang, Sun et al (2015). reported that the acute toxicity to Scenedesmus obliquus could be reduced in municipal WWTPs in northeast China.…”
mentioning
confidence: 70%